Silicon-oxygen-carbon composite material, preparation method thereof and lithium ion battery negative electrode material
Patent Information
- Application Number
- CN202611121177.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]然而,传统的硅氧碳复合负极材料多采用溶胶-凝胶、聚硅氧烷裂解等方法制备,这类制备方式存在明显弊端:一是原料成本高昂,聚硅氧烷等前驱体价格昂贵,导致材料规模化生产的经济性较差;二是碳相分布不均,制备过程中碳源难以均匀分散于硅氧基质中,易形成碳富集或碳缺陷区域,影响材料导电性与结构稳定性的均一性;三是热解过程易产生游离氧化硅,高温热解阶段硅氧键易发生断裂重组,生成的游离氧化硅为绝缘相,会显著降低材料的电子与离子传导效率,进而恶化电池的倍率性能与循环稳定性
1.本申请的硅氧碳复合材料由无定形Si–O–C连续相、自由碳相、Si-C相和Ni–Si纳米相组成,自由碳相呈均匀分散,且降低了热解中游离氧化硅的形成,使得材料兼具高容量与结构稳定性,提高电池的倍率性能与循环稳定性,拓宽了硅氧碳复合材料的商业化应用。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This application relates to a silicon-oxygen-carbon composite material and its preparation method, as well as a lithium-ion battery anode material, belonging to the fields of new energy materials and lithium-ion battery technology. Background Technology
[0002] With the rapid development of the new energy industry, lithium-ion batteries are increasingly widely used in consumer electronics, power batteries, and energy storage. Market demands for battery energy density, cycle life, and safety are continuously increasing. As a core component of lithium-ion batteries, the performance of the anode material directly determines the overall quality of the battery. Among various anode materials, pure silicon (Si) is considered a key candidate material for improving the energy density of lithium-ion batteries due to its extremely high theoretical specific capacity (approximately 4200 mAh / g, more than 10 times that of commercial graphite anodes), making it a hot research topic in the industry.
[0003] However, the practical commercial application of pure silicon materials is severely constrained by their inherent defects, mainly in the following aspects: First, the volume expansion effect is significant. The volume expansion rate of pure silicon during lithium-ion insertion / extraction can reach over 300%. Repeated volume changes can lead to electrode structure cracking and silicon particle pulverization, damaging the integrity of the electrode. Second, the electrode conductivity is poor. Pure silicon is a semiconductor material with low electronic conductivity, resulting in a large charge transfer impedance during battery charging and discharging, affecting rate performance. Third, the interface stability is poor. The electrode structure damage caused by volume expansion leads to repeated rupture and regeneration of the solid electrolyte interphase (SEI) film, exacerbating electrolyte consumption, reducing battery coulombic efficiency, and causing continuous capacity decay, severely shortening battery cycle life. Although the industry has modified pure silicon materials through nano-sizing and porous structure design, problems such as high preparation costs and difficulty in large-scale production still exist, making it difficult to meet the needs of practical applications.
[0004] To address the aforementioned shortcomings of pure silicon materials, researchers have developed various silicon-based composite anode materials, among which silicon-oxygen-carbon (SiOC) composite anode materials stand out due to their unique composition and structural advantages. SiOC materials construct a multi-component composite matrix structure by introducing oxygen and carbon phases into the silicon phase system. On one hand, oxygen forms stable silicon-oxygen bonds with silicon, generating buffer substances such as lithium oxide and lithium silicate, effectively mitigating volume expansion during lithium-ion insertion / extraction, significantly reducing the expansion rate to below 200%, and even achieving near-zero volume strain, thus ensuring electrode structural stability. On the other hand, the carbon phase (such as graphite, hard carbon, and carbon nanotubes) not only constructs continuous electron transport channels, significantly improving the material's conductivity, but also acts as a physical barrier to reduce direct contact between silicon and the electrolyte, inhibiting repeated rupture of the SEI film and improving interface stability. Furthermore, the synergistic effect of silicon, oxygen, and carbon optimizes lithium-ion diffusion kinetics, significantly improving battery cycle life and coulombic efficiency while ensuring a high specific capacity (typically 1500-1800 mAh / g). Therefore, silicon-oxygen-carbon composite anode materials have become the preferred solution for balancing high energy density and long cycle stability, which is of great significance for promoting the development of high-performance lithium-ion batteries.
[0005] However, traditional silicon-oxygen-carbon composite anode materials are mostly prepared using sol-gel and polysiloxane pyrolysis methods. These methods have significant drawbacks: First, the raw material costs are high, with expensive precursors such as polysiloxanes, resulting in poor economic efficiency for large-scale production. Second, the carbon phase distribution is uneven, as the carbon source is difficult to disperse uniformly in the silicon-oxygen matrix during preparation, easily forming carbon-enriched or carbon-defect regions, affecting the uniformity of the material's conductivity and structural stability. Third, the pyrolysis process easily generates free silicon oxide. During high-temperature pyrolysis, silicon-oxygen bonds are prone to breakage and recombination, and the generated free silicon oxide is an insulating phase, which significantly reduces the material's electronic and ion conduction efficiency, thereby deteriorating the battery's rate performance and cycle stability.
[0006] In summary, the existing silicon-oxygen-carbon composite anode material preparation technology still has many problems that need to be solved, which limits its further commercial application. Summary of the Invention
[0007] To address the aforementioned issues, a silicon-oxygen-carbon composite material and its preparation method are provided. This silicon-oxygen-carbon composite material is composed of an amorphous Si–O–C continuous phase, a free carbon phase, a Si-C phase, and a Ni–Si nanophase. It is a silicon-oxygen-carbon composite material that combines structural stability and electrochemical activity, reducing the formation of pyrolytic free silicon oxide and improving the rate performance and cycle stability of the battery.
[0008] According to a first aspect of this application, a silicon-oxygen-carbon composite material is provided, wherein the elemental composition of the silicon-oxygen-carbon composite material is: Si 35–45 wt%, O 10–25 wt%, C 25–40 wt%, Ni 5–20 wt%; The silicon-oxygen-carbon composite material is composed of the following structural units: amorphous Si–O–C continuous phase, free carbon phase, Si-C phase, and Ni–Si nanophase.
[0009] In the silicon-oxygen-carbon composite material of this application, the free carbon phase, Si-C phase, and Ni-Si nanophase are uniformly dispersed, and the C content in the amorphous Si-O-C continuous phase is greater than that in the free carbon phase, while the Si content in the amorphous Si-O-C continuous phase is greater than that in the Si-C phase. Compared with existing silicon-oxygen-carbon composite materials, the uniform dispersion of the free carbon phase in this silicon-oxygen-carbon composite material improves the uniformity of the material's conductivity and structural stability. Under the above-mentioned elemental constraints, the conductivity of the silicon-oxygen-carbon composite material can be increased, and a rigid skeleton can be provided to suppress expansion during charging and discharging, ensuring a uniform Si-O-C phase and avoiding powder shedding due to insufficient rigidity and charging expansion.
[0010] Optionally, the elemental composition of the silicon-oxygen-carbon composite material is: Si 35.8-45 wt%, O 10.2-23.9 wt%, C 25.2-38.9 wt%, Ni 5.4-20.00 wt%.
[0011] Optionally, the particle size of the Ni–Si nanophase is 5-500 nm.
[0012] Optionally, the average specific surface area of the silicon-oxygen-carbon composite material is 45–80 m²·g. - ¹.
[0013] The specific surface area of this silicon-oxygen-carbon composite material is within the above range, which can increase the electrolyte contact area and improve the ion transport efficiency without causing the SEI film to consume too much lithium and reduce the initial efficiency.
[0014] Optionally, the electrical conductivity of the silicon-oxygen-carbon composite material is ≥1.1×10⁻⁶. - ³ S·cm - ¹.
[0015] This silicon-oxygen-carbon composite material has high electrical conductivity, which can significantly improve the conductivity of the negative electrode material, thereby improving the rate performance of the battery, and also improving the cycle stability and coulombic efficiency of the battery.
[0016] Optionally, the specific capacity of the battery anode material prepared by the silicon-oxygen-carbon composite material is 550 mAh·g. -¹Above, the coulombic efficiency in the first week is ≥70%, and the capacity retention rate after 200 cycles is ≥70%.
[0017] Preferably, the battery anode material prepared by the silicon-oxygen-carbon composite material has a first-cycle coulombic efficiency of ≥74% and a capacity retention rate of ≥80% after 200 cycles.
[0018] The anode material prepared by this silicon-oxygen-carbon composite material exhibits high specific capacitance, cycle stability, and coulombic efficiency, which broadens the application prospects of this composite material and enhances the commercial value of the anode material.
[0019] According to a second aspect of this application, a method for preparing a silicon-oxygen-carbon composite material is provided, comprising the following steps: (1) Dissolve polysiloxane in a solvent, add carbon source and nickel source and stir to form a mixture; (2) Add silicon carbide powder to the mixture in step (1) and disperse it ultrasonically to obtain a slurry. Then dry the slurry and pre-crosslink it at 200–400°C for at least 2 hours. (3) Under the protection of inert gas, the pre-crosslinked product of step (2) is heated to 900-1000℃ and kept at that temperature for at least 0.5h, then cooled, washed and dried to obtain the product.
[0020] In the preparation method of this application, the stable structural properties of silicon carbide are utilized. A Si–O–C network is introduced through polysiloxane, and a carbon source and a metal catalyst are used for catalytic activation and chemical reaction to generate a silicon-oxygen-carbon composite that possesses both structural stability and electrochemical activity. The nickel source in the slurry is in the form of Ni. 2+ It exists and can generate Ni nanophase during carbonization and reduction, promoting Si–C bond breaking and Si–O–C network formation, thereby realizing the structural reforming of silicon-oxygen-carbon composite materials. At the same time, it can also react with silicon carbide to produce Si-Ni phase, improving the capacity of composite materials.
[0021] The pre-crosslinking in step (2) is the pre-crosslinking of carbon source and nickel source. This pre-crosslinking is for the pyrolysis of carbon source and the reduction reaction of nickel source. Therefore, the pre-crosslinking time should be at least 2 hours to ensure sufficient reaction. The heat preservation process in step (3) can carbonize carbon source to generate continuous conductive carbon skeleton, enhance the electronic conduction of composite material, and generate Ni-Si nano phase, thereby obtaining silicon-oxygen-carbon composite material with improved structural stability and electrochemical performance. The heat preservation time in step (3) only needs to be more than 2 hours. Extending the heat preservation time has little impact on the performance of the material.
[0022] Optionally, the mass ratio of the nickel source, silicon carbide powder, polysiloxane and carbon source is (1-3):1:(1-5):(0.5-3), preferably (1-2.7):1:(1-4.7):(0.6-2.7).
[0023] Under the above ratios, the proportions of the four phases and elemental proportions in the silicon-oxygen-carbon composite material can meet the aforementioned defined ranges, resulting in the formation of the optimal silicon-oxygen-carbon composite material. If the polysiloxane content is too low, the oxygen content and the proportion of the amorphous Si–O–C continuous phase will be smaller, and vice versa; if the carbon source content is too low, the carbon content and the proportion of the free carbon phase will be smaller, and vice versa.
[0024] Nickel sources catalyze the reaction of silicon carbide and polysiloxane to form silicon-oxygen-carbon composites, achieving structural reforming of silicon in both materials. This significantly improves the structural stability and electrochemical performance of the silicon-oxygen-carbon composite. Simultaneously, nickel can react with silicon carbide to form a nickel-silicon composite phase, increasing battery capacity, while unreacted silicon carbide provides structural strength. The amount of nickel source added is crucial for its optimal performance. Insufficient nickel content leads to decreased structural stability and electrochemical performance, resulting in a low capacity due to insufficient nickel-silicon composite phase formation. Conversely, excessive nickel content increases costs and can lead to the formation of a high-nickel-silicon composite phase, resulting in capacity loss, poor cycle performance, and damage to the silicon-oxygen-carbon structure. Therefore, the amount of nickel source added should not be excessive.
[0025] Optionally, the heating rate in step (2) to 900-1000℃ is 1-10°C / min.
[0026] When the carbon source is glucose, fructose, maltose, sucrose, or resin, this setting is to ensure stable gas production during the reaction process and avoid excessively rapid gas production caused by rapid temperature rise, which could lead to runaway reaction, reduced catalytic efficiency, and consequently, a decline in the performance of the silicon-oxygen-carbon composite material.
[0027] Preferably, in step (3), the heating rate of the pre-crosslinked product from step (2) to 900-1000°C is 1-5°C / min, more preferably 2-3°C / min.
[0028] Optionally, the pre-crosslinking time in step (2) is 2-3 hours.
[0029] Optionally, the heat preservation time in step (3) is 0.5-3h.
[0030] The pre-crosslinking time and the holding time during heating can shorten the total production time of silicon-oxygen-carbon composite materials, thereby reducing production costs.
[0031] Optionally, the silicon carbide powder is silicon carbide powder obtained by crushing silicon carbide waste.
[0032] Silicon carbide powder with a purity of less than 99% is often used as waste. The silicon carbide powder of the silicon-oxygen-carbon composite material of this application can be prepared from waste silicon carbide powder, and its performance is not significantly reduced compared with silicon carbide powder with a purity of more than 99%. This method can further reduce the production cost of silicon-oxygen-carbon composite material and realize the recycling of silicon carbide waste, which has great practical significance.
[0033] Optionally, the particle size of the silicon carbide powder is not greater than 1 µm, preferably 100-500 nm.
[0034] Optionally, the carbon source is selected from at least one of glucose, fructose, sucrose, phenolic resin, urea-formaldehyde resin, furan resin, lignin, and starch; The nickel source is selected from at least one of nickel nitrate, nickel nitrate hydrate, nickel sulfate, nickel sulfate hydrate, nickel acetate, and nickel acetate hydrate.
[0035] According to a third aspect of this application, a lithium-ion battery anode material is provided, comprising the silicon-oxygen-carbon composite material described in any one of the preceding claims or the silicon-oxygen-carbon composite material prepared by any one of the preceding claims.
[0036] Optionally, the specific capacity of the lithium-ion battery anode material is 550 mAh·g. - ¹Above, the coulombic efficiency in the first week is ≥70%, and the capacity retention rate after 200 cycles is ≥80%.
[0037] The beneficial effects of this application include, but are not limited to: 1. The silicon-oxygen-carbon composite material of this application is composed of an amorphous Si–O–C continuous phase, a free carbon phase, a Si-C phase and a Ni–Si nano phase. The free carbon phase is uniformly dispersed and reduces the formation of free silicon oxide during pyrolysis, so that the material has both high capacity and structural stability, improves the rate performance and cycle stability of the battery, and broadens the commercial application of silicon-oxygen-carbon composite materials.
[0038] 2. The preparation method of the silicon-oxygen-carbon composite material of this application: Silicon carbide has a strong structure due to its stable covalent bonds, but it has the defect of low activity when used directly as an electrode. Based on silicon carbide, polysiloxane is introduced into the Si–O–C network, and carbon source and nickel source are added to generate a silicon-oxygen-carbon composite material with both structural stability and electrochemical activity.
[0039] 3. The preparation method of silicon-oxygen-carbon composite material of this application develops a controllable carbothermal conversion method using silicon carbide as silicon source and Ni as catalyst, thereby obtaining a silicon-oxygen-carbon based composite material with improved structural stability and electrochemical activity, which is of great significance for the commercial application of silicon-oxygen-carbon materials in batteries.
[0040] 4. In the preparation method of the silicon-oxygen-carbon composite material of this application, the addition of nickel source can not only catalyze the formation of silicon nanowires from silicon and carbon nanotubes from carbon, but also promote the structural reforming of silicon carbide and polysiloxane, and generate Si-Ni composite phase, thereby improving the structural stability and capacity of silicon-oxygen-carbon composite material. Detailed Implementation
[0041] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.
[0042] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application were all purchased commercially. The waste silicon carbide powder used in the following embodiments and comparative examples refers to silicon carbide powder obtained by crushing silicon carbide waste, in which the silicon carbide content is 95-99%, and other impurity phases are carbon and / or silicon.
[0043] The polysiloxanes used in the following examples and comparative examples are commercially available polysiloxanes, which can be in powder or liquid form, and can achieve the same test results under the same preparation process.
[0044] Unless otherwise specified, the methods used in the embodiments and comparative examples of this application are conventional methods in the prior art.
[0045] Example 1 This embodiment relates to a method for preparing a silicon-oxygen-carbon composite material, including the following steps: (1) Dissolve 50g of polysiloxane in ethanol solvent, add 30g of phenolic resin (molecular weight 3000) and 20g of nickel nitrate hexahydrate and stir to form a mixture; (2) Add 20g of waste silicon carbide powder (particle size D50=1.0µm) to the mixture in step (1) and ultrasonically disperse for 30min to obtain a slurry. Then dry the slurry and pre-crosslink it at 400°C for 1h. (3) Under the protection of inert nitrogen gas, the pre-crosslinked product of step (2) is heated to 900°C and kept at a heating rate of 5°C / min for 0.5h. Then it is cooled to room temperature, washed three times with pure water, and dried to constant weight to obtain the product.
[0046] Example 2 This embodiment relates to a method for preparing a silicon-oxygen-carbon composite material, including the following steps: (1) Dissolve 70g of polysiloxane in ethanol solvent, add 40g of urea-formaldehyde resin (molecular weight of 1000) and 35g of nickel sulfate and stir to form a mixture; (2) Add 20g of waste silicon carbide powder (particle size D50=0.50µm) to the mixture in step (1) and ultrasonically disperse for 30min to obtain a slurry. Then dry the slurry and pre-crosslink it at 200°C for 1h. (3) Under the protection of inert nitrogen gas, the pre-crosslinked product of step (2) is heated to 950°C and kept at a heating rate of 1°C / min for 1 hour. Then it is cooled to room temperature, washed three times with pure water, and dried to constant weight to obtain the product.
[0047] Example 3 This embodiment relates to a method for preparing a silicon-oxygen-carbon composite material, including the following steps: (1) Dissolve 30g of polysiloxane in ethanol solvent, add 10g of furan resin (molecular weight 2000) and 15g of nickel sulfate hexahydrate and stir to form a mixture; (2) Add 15g of waste silicon carbide powder (particle size D50=0.50µm) to the mixture in step (1) and ultrasonically disperse for 30min to obtain a slurry. Then dry the slurry and pre-crosslink it at 300°C for 3h. (3) Under the protection of inert nitrogen gas, the pre-crosslinked product of step (2) is heated to 1000℃ and kept at a heating rate of 5°C / min for 0.5h. Then it is cooled to room temperature, washed three times with pure water, and dried to constant weight to obtain the product.
[0048] Example 4 This embodiment relates to a method for preparing a silicon-oxygen-carbon composite material, including the following steps: (1) Dissolve 16g of polysiloxane in ethanol solvent, add 30g of glucose powder and 25g of nickel nitrate and stir to form a mixture; (2) Add 15g of waste silicon carbide powder (particle size D50=0.50µm) to the mixture in step (1) and ultrasonically disperse for 30min to obtain a slurry. Then dry the slurry and pre-crosslink it at 400°C for 1h. (3) Under the protection of inert nitrogen gas, the pre-crosslinked product of step (2) is heated to 900°C and kept at a heating rate of 3°C / min for 3 hours. Then it is cooled to room temperature, washed three times with pure water, and dried to constant weight to obtain the product.
[0049] Example 5 This embodiment relates to a method for preparing a silicon-oxygen-carbon composite material, including the following steps: (1) Dissolve 20g of polysiloxane in ethanol solvent, add 15g of starch and 10g of nickel acetate and stir to form a mixture; (2) Add 6g of waste silicon carbide powder (particle size D50=0.50µm) to the mixture in step (1) and ultrasonically disperse for 30min to obtain a slurry. Then dry the slurry and pre-crosslink it at 400°C for 1h. (3) Under the protection of inert nitrogen gas, the pre-crosslinked product of step (2) is heated to 950°C and kept at a heating rate of 5°C / min for 0.5h. Then it is cooled to room temperature, washed three times with pure water, and dried to constant weight to obtain the product.
[0050] Example 6 This embodiment relates to a method for preparing a silicon-oxygen-carbon composite material, including the following steps: (1) Dissolve 40g of polysiloxane in ethanol solvent, add 40g of lignin and 20g of nickel acetate dihydrate and stir to form a mixture; (2) Add 20g of waste silicon carbide powder (particle size D50=0.50µm) to the mixture in step (1) and ultrasonically disperse for 30min to obtain a slurry. Then dry the slurry and pre-crosslink it at 200°C for 3h. (3) Under the protection of inert nitrogen gas, the pre-crosslinked product of step (2) is heated to 920°C and kept at a heating rate of 1°C / min for 2 hours. Then it is cooled to room temperature, washed three times with pure water, and dried to constant weight to obtain the product.
[0051] Example 7 This embodiment relates to a method for preparing a silicon-oxygen-carbon composite material, including the following steps: (1) Dissolve 40g of polysiloxane in ethanol solvent, add 30g of glucose powder and 20g of nickel nitrate and stir to form a mixture; (2) Add 15g of waste silicon carbide powder (particle size D50=0.50µm) to the mixture in step (1) and ultrasonically disperse for 30min to obtain a slurry. Then dry the slurry and pre-crosslink it at 300°C for 1h. (3) Under the protection of inert nitrogen gas, the pre-crosslinked product of step (2) is heated to 970°C and kept at a heating rate of 5°C / min for 1.5h. Then it is cooled to room temperature, washed three times with pure water, and dried to constant weight to obtain the product.
[0052] Example 8 The difference between this embodiment and Embodiment 7 is that the amount of glucose powder added is 40g, while the rest is the same as in Embodiment 7.
[0053] Example 9 The difference between this embodiment and Embodiment 7 is that the amount of polysiloxane added is 70g, while the rest is the same as in Embodiment 7.
[0054] Example 10 This embodiment relates to a method for preparing a silicon-oxygen-carbon composite material, including the following steps: (1) Dissolve 40g of polysiloxane in ethanol solvent, add 20g of glucose powder and 20g of nickel nitrate and stir to form a mixture; (2) Add 15g of waste silicon carbide powder (particle size D50=0.50µm) to the mixture in step (1) and ultrasonically disperse for 30min to obtain a slurry. Then dry the slurry and pre-crosslink it at 300°C for 1.5h. (3) Under the protection of inert nitrogen gas, the pre-crosslinked product of step (2) is heated to 910°C and kept at a heating rate of 5°C / min for 2.5h. Then it is cooled to room temperature, washed three times with pure water, and dried to constant weight to obtain the product.
[0055] Example 11 The difference between this embodiment and embodiment 10 is that the heating rate in step (3) is 15°C / min.
[0056] Example 12 The difference between this embodiment and Example 10 is that the amount of nickel nitrate added is 40 grams.
[0057] Example 13 The difference between this embodiment and embodiment 10 is that the heat preservation time in step (3) is 5 hours.
[0058] Comparative Example 1 The difference between this comparative example and Example 4 is that nickel nitrate is not added.
[0059] Comparative Example 2 The difference between this comparative example and Example 4 is that glucose powder is not added.
[0060] Comparative Example 3 The difference between this comparative example and Example 4 is that in step (3), the temperature is raised to 850°C and kept at that temperature for 3 hours.
[0061] Comparative Example 4 The difference between this comparative example and Example 4 is that step (2) involves drying the slurry and then proceeding directly to step (3), i.e., without pre-crosslinking.
[0062] Comparative Example 5 The difference between this comparative example and Example 4 is that the pre-crosslinking temperature in step (2) is 500°C.
[0063] Test Example 1 The silicon-oxygen-carbon composite materials prepared in the above embodiments and comparative examples were tested for elemental content, specific surface area, and electrical conductivity. The test results are shown in Table 1. The specific test methods are as follows: Elemental content testing: Silicon and nickel were measured using atomic absorption spectrometry, while oxygen and carbon were measured using infrared absorption spectrometry under high-temperature release.
[0064] Specific surface area test: Nitrogen adsorption-desorption BET method was used.
[0065] Conductivity test: The four-probe method was used for testing.
[0066] Table 1
[0067] Test Example 2 Using the silicon-oxygen-carbon composite materials prepared in the above examples and comparative examples as active materials, lithium-ion battery anode materials were prepared according to the following composition: active material: 80 wt%; conductive agent Super P: 10 wt%; PVDF: 10 wt%. The density after coating was 1.0 g / cm³. 2 .
[0068] Battery tests were conducted on the negative electrode materials prepared in the above embodiments and comparative examples. The test results are shown in Table 2. The test methods are as follows: Assemble CR2032 coin cells, with lithium foil used for the motor; electrolyte: 1.0 M LiPF6 + EC + DEC + 10wt% FEC; separator: Celgard 2400; voltage window: 0.01–2.0V. After assembly, the efficiency was measured by two cycles of charge and discharge at 0.1C, followed by 100 cycles at 0.5C to record the capacity.
[0069] Table 2
[0070] Due to the presence of some impurities within the system, the sum of the contents of silicon, oxygen, carbon, and nickel in Table 1 is less than 100%. Based on the above test results, the silicon-oxygen-carbon composite material of this application possesses both structural stability and electrochemical activity, and the specific capacity of the battery anode material prepared from it is 550 mAh·g. - ¹Above, the coulombic efficiency in the first week is ≥70%, and the capacity retention rate after 200 cycles is ≥80%.
[0071] A comparison of Examples 8, 9 and Example 7 shows that increasing the carbon source will improve conductivity and increase specific surface area, but reduce the initial efficiency. Increasing the amount of polysiloxane added will lead to a decrease in the specific surface area of the silicon-oxygen-carbon composite material, which will improve the specific capacity and the first-cycle coulombic efficiency, but reduce conductivity and cycling performance.
[0072] According to the comparison between Example 11 and Example 10, the heating rate in step (3) is too fast, which will accelerate the decomposition of the carbon source, reduce the specific surface area and conductivity of the silicon-oxygen-carbon composite material, and thus lead to a decrease in the electrochemical performance of the negative electrode material.
[0073] A comparison of Examples 12 and 10 shows that if the amount of nickel source added is too high, the specific surface area of the silicon-oxygen-carbon composite material will not change much. However, the increase of nickel will not improve the specific capacity of the anode material. Moreover, due to the excessive amount of nickel added, the amorphous Si–O–C continuous phase will decrease, and a high-nickel Ni-Si inert phase will be generated. As a result, the specific capacity, first-cycle coulombic efficiency and capacity retention rate after 200 cycles in Table 2 will all decrease.
[0074] According to the comparison between Example 13 and Example 10, the extension of the heat preservation time in step (3) has little effect on the electrochemical performance of the silicon-oxygen-carbon composite material and the negative electrode material prepared therefrom, but it will prolong the production time and thus increase the production cost.
[0075] The comparison between Comparative Example 1 and Example 4 shows that the addition of a nickel source can promote the activation of SiC and the formation of the Si–O–C network, thereby improving the structural stability and electrochemical performance of the silicon-oxygen-carbon composite material.
[0076] The comparison between Comparative Example 2 and Example 4 shows that the carbon source can form a three-dimensional conductive network, resulting in a high free carbon content, which significantly improves the capacity retention and specific capacity after 200 cycles.
[0077] According to the comparison between Comparative Example 3 and Example 4, the heat preservation temperature in step (3) will affect the carbonization and reduction process, thereby reducing the electrochemical performance of the silicon-oxygen-carbon composite material.
[0078] Based on the comparison of Comparative Examples 4 and 5 and Example 4, it can be seen that pre-crosslinking can stabilize the catalyst, thereby improving the catalytic efficiency. If the pre-crosslinking temperature is too high, the catalyst and silicon carbide are easily separated, resulting in low catalytic efficiency and affecting the electrochemical performance of the silicon-oxygen-carbon composite material.
[0079] The above description is merely an embodiment of this application, and the scope of protection of this application is not limited to these specific embodiments, but is determined by the claims of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the technical concept and principles of this application should be included within the scope of protection of this application.
Claims
1. A silicon-oxygen-carbon composite material, characterized in that, The elemental composition of the silicon-oxygen-carbon composite material is: Si 35–45 wt%, O 10–25 wt%, C 25–40 wt%, Ni 5–20 wt%. The silicon-oxygen-carbon composite material is composed of the following structural units: amorphous Si–O–C continuous phase, free carbon phase, Si-C phase, and Ni–Si nanophase.
2. The silicon-oxygen-carbon composite material according to claim 1, characterized in that, The average specific surface area of the silicon-oxygen-carbon composite material is 45–80 m². 2 ·g -1 .
3. The silicon-oxygen-carbon composite material according to claim 1, characterized in that, The electrical conductivity of the silicon-oxygen-carbon composite material is ≥1.1×10⁻⁶. - ³ S·cm -1 .
4. The silicon-oxygen-carbon composite material according to claim 1, characterized in that, The specific capacity of the battery anode material prepared from the silicon-oxygen-carbon composite material is 550 mAh·g. - ¹Above, the coulombic efficiency in the first week is ≥70%, and the capacity retention rate after 200 cycles is ≥70%.
5. A method for preparing a silicon-oxygen-carbon composite material, characterized in that, Includes the following steps: (1) Dissolve polysiloxane in a solvent, add carbon source and nickel source and stir to form a mixture; (2) Add silicon carbide powder to the mixture in step (1) and disperse it ultrasonically to obtain a slurry. Then dry the slurry and pre-crosslink it at 200–400°C for at least 2 hours. (3) Under the protection of inert gas, the pre-crosslinked product of step (2) is heated to 900-1000℃ and kept at that temperature for at least 0.5h, then cooled, washed and dried to obtain the product.
6. The preparation method according to claim 5, characterized in that, The mass ratio of the nickel source, silicon carbide powder, polysiloxane and carbon source is (1-3):1:(1-5):(0.5-3).
7. The preparation method according to claim 5, characterized in that, In step (3), the pre-crosslinked product from step (2) is heated to 900-1000°C at a rate of 1-10°C / min; and / or The pre-crosslinking time in step (2) is 2-3 hours.
8. The preparation method according to claim 5, characterized in that, The silicon carbide powder is silicon carbide powder obtained by crushing silicon carbide waste; and / or The particle size of the silicon carbide powder is no greater than 1 µm.
9. A lithium-ion battery anode material, characterized in that, It includes the silicon-oxygen-carbon composite material according to any one of claims 1-4 or the silicon-oxygen-carbon composite material prepared by the preparation method according to any one of claims 5-8.
10. The lithium-ion battery anode material according to claim 9, characterized in that, The specific capacity of the lithium-ion battery anode material is 550 mAh·g. - ¹Above, the coulombic efficiency in the first week is ≥70%, and the capacity retention rate after 200 cycles is ≥80%.